2017
DOI: 10.1007/s10843-017-0214-3
|View full text |Cite
|
Sign up to set email alerts
|

Entrepreneurship, economic development, and institutional environment: evidence from OECD countries

Abstract: The purpose of this article is to establish a typology of entrepreneurship for OECD countries over the 1999-2012 period. Our aim is to draw a distinction between managerial and entrepreneurial economies, to identify groups of countries with similar economic and entrepreneurial activity variables, and to determine the economic and institutional drivers of entrepreneurial activities in each group. We show that the level of development, sectoral specialization, and institutional variables related to entrepreneurs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 56 publications
(47 reference statements)
0
17
0
2
Order By: Relevance
“…Covin and Miller (2014) argue that cross-national differences in EO can be best investigated by the use of institutional theory. It can be suggested that the extent to which institutions offer support to entrepreneurial firms is a major reason for differences in EO between developed and emerging markets (Abdesselam et al 2018;Tiwari and Korneliussen 2018). Entrepreneurial firms located in emerging or fragile markets often suffer from institutional burdens due to underdeveloped or non-existent external support (Clercq et al 2010).…”
Section: Institutional Environment and Eomentioning
confidence: 99%
“…Covin and Miller (2014) argue that cross-national differences in EO can be best investigated by the use of institutional theory. It can be suggested that the extent to which institutions offer support to entrepreneurial firms is a major reason for differences in EO between developed and emerging markets (Abdesselam et al 2018;Tiwari and Korneliussen 2018). Entrepreneurial firms located in emerging or fragile markets often suffer from institutional burdens due to underdeveloped or non-existent external support (Clercq et al 2010).…”
Section: Institutional Environment and Eomentioning
confidence: 99%
“…A potential reason for a variation in the importance of personal factors for either entrepreneurial intention or status can be found within the institutional environments themselves. As highlighted by previous researchers, variations in institutional environments that characterize countries may contribute to explaining inconsistencies in previous findings on entrepreneurial intention and/or entrepreneurial status (e.g., Dehghanpour Farashah 2015; Terjesen et al 2013;Carsrud and Brännback 2011;Shook et al 2003;Abdesselam et al 2018;Baughn and Neupert 2003). According to the institutional perspective on entrepreneurship (e.g., North 1991), the explanation of entrepreneurial activity (i.e., entrepreneurs versus non-entrepreneurs) requires the consideration of the situational context in the different nations, as in order for entrepreneurial intentions to translate into actual activity, they must be matched with the prevailing entrepreneurial opportunities (Shane and Venkataraman 2000), which are conditional on the quality of national institutions.…”
Section: Entrepreneurial Intention and Status In Different Entrepreneurial Environmentsmentioning
confidence: 93%
“…The business environment as perceived by enterprises varies across countries (Abdesselam et al, 2018;Ayyagari et al, 2007;Bartelsman et al, 2010;Dilli et al, 2018). Accordingly, the influence of social factors on entrepreneurship is perceived by firms differently across regions and countries (Pinho, 2017;Zygmunt, 2018;Androniceanu, 2019;Pinho, 2017).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Entrepreneurship is widely acknowledged as an engine of economy, as it contributes directly to employment rate and economic growth (Abdesselam et al, 2018;Acs et al, 2018;Bosma et al 2018). Indeed, small and medium-sized enterprises (SMEs) are vital for the European Union economies, as they generate 56.8% of the value added and employ 66.4% of the working force (European Commission, 2018).…”
Section: Introductionmentioning
confidence: 99%